Postoperative Evaluation of Bilateral Reading Performance With Two Intraocular Lenses: Twelve-Month Results - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Purpose: The aim of this study was to compare the bilateral reading performances within the first 12 months after the implantation of two intraocular lens (IOL) models. Methods: The patients involved in this research had bilateral phacoemulsification and implantation of the Acriva Reviol MFM 613 IOL (group 1) or AcrySof ReSTOR SN6AD1 apodized multifocal IOL (group 2). The bilateral reading performance was evaluated preoperatively and postoperatively using the MNREAD acuity charts. The reading speed, critical print size, and reading acuity were measured binocularly at 40 and 60 cm. In addition, the binocular uncorrected visual acuities (far, UDVA; intermediate, UIVA; and near, UNVA) were also measured. Results: Each IOL model was implanted in 30 eyes (15 patients), and 30 patients were included in this study. Overall, there were no statistically significant postoperative differences in the mean UDVA, UIVA and mean (P>0.05). There were statistically significant postoperative differences in the mean reading acuity (group 1, 0.07 +/- 0.10 logMAR; group 2, 0.02 +/- 0.08 logMAR; P = 0.019) at 40 cm. When tested at 60 cm, the reading acuity (0.136 +/- ogMAR and 0.39 +/- 0.16 logMAR, respectively; P = 0.005) were significantly better in group 1 than in group 2. Conclusion: Both of the IOLs achieved good visual performances. However, the Acriva Reviol MFM 613 IOL performed better than the AcrySof ReSTOR SN6AD1 at an intermediate distance, whereas the AcrySof ReSTOR SN6AD1 provided better near distance results.
Keywords: Cataract; MNREAD acuity chart; Multifocal intraocular lenses; VISUAL PERFORMANCE; IMPLANTATION; OUTCOMES; PSYCHOPHYSICS; RESTOR; ACUITY; MODELS